Biological monitoring of exposure to rare earth elements and selected metals in the Inuit population of Nunavik, Canada. (February 2022) - Cirtiu, Ciprian Mihai; Valcke, Mathieu; Gagné, Michelle; Bourgault, Marie-Hélène; Narame, Céline; Gadio, Souleymane; Poulin, Patrick; Ayotte, Pierre
Abstract: In Nunavik (Northern Quebec, Canada), some mining projects are envisioned, that could increase the contamination of the environment by various chemicals, including rare earth elements (REEs), and implicitly Inuit population exposure. The objective of this study was to determine the baseline biological exposure of the population to these elements, before the potential mining development occurs. In the framework of the 2017 Qanuilirpitaa ? Inuit health survey, urine samples were obtained from a representative sample of the adult Nunavik population, which were used to constitute 30 pooled samples according to age, sex and Nunavik subregions. Pooled samples were analyzed using sensitive and accurate methods involving ICP-MS platforms to quantify urinary concentrations of 17 REEs and 7 elements of interest in Nunavik (arsenic, antimony, chromium, cobalt, nickel, thallium and uranium). REEs were mostly not detected in pooled samples from this population. Detectable concentrations were found in some samples for cerium (range: 0.5–0.7 nmol/L; 27% > method detection limit (MDL) and lanthanum (range: 0.2–0.4 nmol/L; 33% > MDL). As for the other elements of interest, antimony, arsenic, cobalt and thallium were detected in 100% of the samples, whereas chromium and nickel were detected in 83% and 80% of the samples, respectively. Concentrations of arsenic (geometric mean (GM) = 0.5 μmol/L) and cobalt (GM = 5.2 nmol/L) were greater than in the general Canadian population; the opposite was observed for nickel (GM = 8.9 nmol/L). Arsenic concentrations increased significantly with age, whereas the opposite trend was observed for nickel and thallium. In this first biomonitoring study focusing on REEs and carried out in a representative sample of the Nunavik population, we found no evidence of significant exposure from pooled samples analysis. These results could eventually be used as baseline values in future studies aiming to assess temporal trends of exposure to REEs. Highlights: Urine samples from the Inuit population of Nunavik were pooled according to subregion, sex and age. Rare earth elements were measured using our newly-developed ICP-MS/MS method. Cerium and lanthanum were detected in ≈30% of the pooled samples, mostly from the Ungava Bay region. As, Co, Cr, Ni, Sb and Tl were measured in most pooled samples (≥80%).